2022
DOI: 10.1002/anie.202209446
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Coordination Single Au Atoms on Ultrathin ZnIn2S4Nanosheets for Selective Photocatalytic CO2Reduction towards CH4

Abstract: Selective CO 2 photoreduction to hydrocarbon fuels such as CH 4 is promising and sustainable for carbonneutral future. However, lack of proper binding strengths with reaction intermediates makes it still a challenge for photocatalytic CO 2 methanation with both high activity and selectivity. Here, low-coordination single Au atoms (Au 1 -S 2 ) on ultrathin ZnIn 2 S 4 nanosheets was synthesized by a complex-exchange route, enabling exceptional photocatalytic CO 2 reduction performance. Under visible light irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 64 publications
0
71
0
Order By: Relevance
“…Apart from the formate product, CPET-induced *COOH intermediate via C-linked pathway also leads to *CO intermediate, which could undergo diverse pathways to generate different products, involving CO product through direct desorption, CH 4 or CH 3 OH products via further CPET processes, and even C 2 + products of C 2 H 4 and CH 3 CH 2 OH via CÀ C coupling. [22][23][24] By contrast, direct electron reduction of CO 2 molecule to CO 2 *À intermediate via O-linked pathway is more attractive, with formate being the sole product. However, the highly negative reduction potential of CO 2 /CO 2 *À , that is, E 0 = À 1.9 V versus reversible hydrogen electrode (vs RHE), makes direct electron transfer to CO 2 one of the most energy-demanding processes.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the formate product, CPET-induced *COOH intermediate via C-linked pathway also leads to *CO intermediate, which could undergo diverse pathways to generate different products, involving CO product through direct desorption, CH 4 or CH 3 OH products via further CPET processes, and even C 2 + products of C 2 H 4 and CH 3 CH 2 OH via CÀ C coupling. [22][23][24] By contrast, direct electron reduction of CO 2 molecule to CO 2 *À intermediate via O-linked pathway is more attractive, with formate being the sole product. However, the highly negative reduction potential of CO 2 /CO 2 *À , that is, E 0 = À 1.9 V versus reversible hydrogen electrode (vs RHE), makes direct electron transfer to CO 2 one of the most energy-demanding processes.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution TEM image collected at the interface between the CoP nanorod and the ZnIn 2 S 4 nanosheet clearly reveals the presence of (111) and (200) planes of CoP and (015) and (009) planes of ZnIn 2 S 4 (Figure d), consistent with the selected-area electron diffraction measurement (Figure S5). HAADF–STEM (Figure e) and corresponding elemental mapping images (Figure f–j) confirm the formation of CoP@ZnIn 2 S 4 coaxial nanorods. These observations demonstrate that a compact heterojunction forms between CoP cores and ZnIn 2 S 4 shells, which would facilitate the construction of charge-transfer channels, thereby promoting efficient charge separation in CoP@ZnIn 2 S 4 coaxial nanorod photocatalysts.…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, the change in the coordination of the active site will affect its binding strength with reactive intermediates. Chen and coworkers 49 have found that the single Au atom with low coordination can stabilize the *CH3 intermediates, thereby leading to the selective CH4 generation from CO2 photoreduction (cf. Fig.…”
Section: Regulating the Generation Of Key Reactivementioning
confidence: 99%
“…Finally, during the reaction process, except for the reduction product, there are oxidation products of oxygen (O2) generated in the absence of the photo-induced hole sacrificial agent (e.g., triethanolamine (TEOA), triethylamine (TEA), etc.) [48][49][50] . The generated O2 would combine with photo-induced electrons to form reactive oxygen species (e.g., •O2…”
Section: Introductionmentioning
confidence: 99%